2018
DOI: 10.1371/journal.pone.0203766
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ten weeks dynamic or isometric core training on climbing performance among highly trained climbers

Abstract: This is the first study to compare the effects of isometric vs. dynamic core training and characterize core-training adaptations using climbing-specific performance and core strength tests in elite climbers. The aim of the study was to compare the effects of attending a progressive core-training program on climbing performance. 19 advanced and elite climbers (7.3±5.6 years climbing experience, red point skill grade 19 IRCRA) were randomized into a dynamic (DCT) or isometric (ICT) core training group and traine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 37 publications
0
23
1
Order By: Relevance
“…The results of this study showed moderate positive correlation of DLL with 40 yard dash and T test. Our finding slightly differs from the results of Sharrock et al (14) where there was a weak positive correlation of DLL with 40 yard dash and T test. This may be due to a small sample size in the study of Sharrock et al (N = 35) and also lower number of male subjects in the study (N = 18).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results of this study showed moderate positive correlation of DLL with 40 yard dash and T test. Our finding slightly differs from the results of Sharrock et al (14) where there was a weak positive correlation of DLL with 40 yard dash and T test. This may be due to a small sample size in the study of Sharrock et al (N = 35) and also lower number of male subjects in the study (N = 18).…”
Section: Discussioncontrasting
confidence: 99%
“…Even though several studies have been conducted to establish the role of core muscles in performance among various sports populations, the (2, 5, 6, 9-12) relationship between core strength or power and sports performance is still a controversial issue. A strong relationship between core and athletic performance has been reported among soccer players, surfing athletes and climbers (13)(14)(15). Nesser et al (5) investigated the relationship between core endurance training and athletic performance among collegiate football players.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account that hand grip-strength and upper arm circumference parameters are widely studied in the elite climbing community indicating superior strength as arm extent in top athletes [ 1 , 6 , 11 , 19 , 20 , 21 ], we chose these parameters to assess whether this could as well be found in recreational climbers. In particular, we felt that athletes performing fitness and ball sports might also show proper overall grip strength, allowing for a better differentiation for what is specifically attributable to the recreational climbing athlete.…”
Section: Methodsmentioning
confidence: 99%
“…The present is one of very few studies (Hermans et al, 2017;Philippe et al, 2019) examining actual climbing performance following climbing-specific training, whereas most of the literature have only assessed strength in climbing-related exercises González-Badillo, 2012, 2019;Medernach et al, 2015;Saeterbakken et al, 2018;Levernier and Laffaye, 2019a). Both groups maintained climbing ability in both disciplines and improved most of the tested variables despite having the same weekly climbing training frequency as before the intervention.…”
Section: Discussionmentioning
confidence: 90%